Polymorphism, Nanostructures, and Barrier Properties of Ceramide-Based Lipid Films - Pullmannová, Petra; Čuříková-Kindlová, Barbora A; Ondrejčeková, Veronika; Kováčik, Andrej; Dvořáková, Kristýna; Dulanská, Lucia; Georgii, Robert; Majcher, Adam; Maixner, Jaroslav; Kučerka, Norbert; Zbytovská, Jarmila; Vávrová, Kateřina (ACS omega, 2023)
Ceramides belong to sphingolipids, an important group of cellular and extracellular lipids. Their physiological functions range from cell signaling to participation in the formation of barriers against water evaporation. In the skin, they are essential for the permeability barrier, together with free fatty acids and cholesterol. We examined the periodical structure and permeability of lipid films composed of ceramides (Cer; namely, N-lignoceroyl 6-hydroxysphingosine, CerNH24, and N-lignoceroyl sphingosine, CerNS24), lignoceric acid (LIG; 24:0), and cholesterol (Chol). X-ray diffraction experiments showed that the CerNH24-based samples form either a short lamellar phase (SLP, d ∼ 5.4 nm) or a medium lamellar phase (MLP, d = 10.63-10.78 nm) depending on the annealing conditions. The proposed molecular arrangement of the MLP based on extended Cer molecules also agreed with the relative neutron scattering length density profiles obtained from the neutron diffraction data. The presence of MLP increased the lipid film permeability to the lipophilic model permeant (indomethacin) relative to the CerNS24-based control samples and the samples that had the same lipid composition but formed an SLP. Thus, the arrangement of lipids in various nanostructures is responsive to external conditions during sample preparation. This polymorphic behavior directly affects the barrier properties, which could also be (patho)physiologically relevant.